Carbon Dioxide Capture with Ionic Liquids and Deep Eutectic Solvents: A New Generation of Sorbents. Issue 2 (30th December 2016) - Sarmad, Shokat; Mikkola, Jyri‐Pekka; Ji, Xiaoyan
Abstract: High cost and high energy penalty for CO2 uptake from flue gases are important obstacles in large‐scale industrial applications, and developing efficient technology for CO2 capture from technical and economic points is crucial. Ionic liquids (ILs) show the potential for CO2 separation owing to their inherent advantages, and have been proposed as alternatives to overcome the drawbacks of conventional sorbents. Chemical modification of ILs to improve their performance in CO2 absorption has received more attention. Deep eutectic solvents (DESs) as a new generation of ILs are considered as more economical alternatives to cope with the deficiencies of high cost and high viscosity of conventional ILs. This Review discusses the potential of functionalized ILs and DESs as CO2 sorbents. Incorporation of CO2 ‐philic functional groups, such as amine, in cation and/or anion moiety of ILs can promot their absorption capacity. In general, the functionalization of the anion part of ILs is more effective than the cation part. DESs represent favorable solvent properties and are capable of capturing CO2, but the research work is scarce and undeveloped compared to the studies conducted on ILs. It is possible to develop novel DESs with promising absorption capacity. However, more investigation needs to be carried out on the mechanism of CO2 sorption of DESs to clarify how these novel sorbents can be adjusted and fine‐tuned to be best tailored as optimized media for CO2 capture. Abstract : Prepare to capture : This Review summarizes the application of ionic liquids (ILs) and deep eutectic solvents (DESs) as a new generation of solvents to capture CO2 with a special focus on improving the performance by functionalization. Owing to the designer nature of ILs and DESs, it is possible to incorporate CO2 ‐philic functional groups or adjust the nature of the hydrogen bond donor to promote the CO2 absorption capacity, respectively. Different possible routes to adequately tune the properties of these materials for optimal CO2 sorption are identified.